2004
DOI: 10.1007/s00204-004-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dioxane on cytochrome P450 enzymes in liver, kidney, lung and nasal mucosa of rat

Abstract: The effect of acute and chronic dioxane administration on hepatic, renal, pulmonary and nasal mucosa P450 enzymes and liver toxicity were investigated in male rats. The acute treatment consisted of two doses (2 g/kg) of dioxane given for 2 days by gavage, whereas the chronic treatment consisted of 1.5% of dioxane in drinking water for 10 days. Both the acute and chronic dioxane treatments induced cytochrome P450 2B1/2- and P450 2E1-dependent microsomal monooxygenase activities (pentoxyresorufin O-depentylase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…CYP2B protein and mRNA are expressed, but not induced by PB, TPD and TCPOBOP in rat and mouse lungs. Several studies have shown the CYP2B-dependent metabolism of substrates in rodent kidneys and brains, although the CYP2B activity is significantly lower than in livers (Nannelli et al 2005;Parmar et al 1998). In our study, despite the presence of very Fig.…”
Section: Discussionmentioning
confidence: 96%
“…CYP2B protein and mRNA are expressed, but not induced by PB, TPD and TCPOBOP in rat and mouse lungs. Several studies have shown the CYP2B-dependent metabolism of substrates in rodent kidneys and brains, although the CYP2B activity is significantly lower than in livers (Nannelli et al 2005;Parmar et al 1998). In our study, despite the presence of very Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, 1,4-dioxane was chosen as a poorly cleared chemical due to its low pulmonary clearance ( P b = 3650) and low hepatic extraction ratio. While benzene is a known substrate of CYP2E1 [18], for which extensive data on interindividual variability are available [19, 20], 1,4-dioxane was included in this study to facilitate the coverage of a range of physico/biochemical properties of potential substrates of CYP2E1 [21]. Chemical-specific parameters are indicated in Table 1 and were taken from the literature [10, 22, 23].…”
Section: Methodsmentioning
confidence: 99%
“…After the end of the inhalation exposure period, the concentration of DX in the tissues was governed primarily by two functions: (1) removal of DX from the blood by exhalation and metabolism in the liver [17,22,[31][32][33][34][35]; and (2) redistribution of DX from the storage tissues into the blood to re-establish equilibrium in the blood as DX was removed from the body.…”
Section: Results and Discussion 31 Inhalation Alone Administration Gmentioning
confidence: 99%